2006
DOI: 10.1139/f06-129
|View full text |Cite
|
Sign up to set email alerts
|

Persistent disturbance by commercial navigation alters the relative abundance of channel-dwelling fishes in a large river

Abstract: We provide the first evidence for chronic effects of disturbance by commercial vessels on the spatial distribution and abundance of fishes in the channels of a large river. Most of the world's large rivers are intensively managed to satisfy increasing demands for commercial shipping, but little research has been conducted to identify and alleviate any adverse consequences of commercial navigation. We used a combination of a gradient sampling design incorporating quasicontrol areas with Akaike's information cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…Additionally, immediate and direct effects of ship traffic via pollution, shear stress, wave splash and sediment turbulences have negative consequences on riverine biota (Smart et at., 1985;Tittizer and Schleuter, 1989;Schaefer et al, 1992;Zauner and Schiemer, 1994;Rütten, 1994). Although these effects are temporal, they induce long-term effects on macrophytes, invertebrates and fish through their high frequency (Holland and Sylvester, 1983;Holland, 1986;Murphy et al, 1995;Ali et al, 1999;Arlinghaus et al, 2002;Wolter and Arlinghaus, 2003;Wolter et al, 2004;Gutreuter et al, 2006). Persistent environmental perturbations have a major impact on the structure and composition of fishes at the community level (ONeill, 1999;Magoulick and Kobza, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immediate and direct effects of ship traffic via pollution, shear stress, wave splash and sediment turbulences have negative consequences on riverine biota (Smart et at., 1985;Tittizer and Schleuter, 1989;Schaefer et al, 1992;Zauner and Schiemer, 1994;Rütten, 1994). Although these effects are temporal, they induce long-term effects on macrophytes, invertebrates and fish through their high frequency (Holland and Sylvester, 1983;Holland, 1986;Murphy et al, 1995;Ali et al, 1999;Arlinghaus et al, 2002;Wolter and Arlinghaus, 2003;Wolter et al, 2004;Gutreuter et al, 2006). Persistent environmental perturbations have a major impact on the structure and composition of fishes at the community level (ONeill, 1999;Magoulick and Kobza, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the abundance of gizzard shad and water temperature were also inversely related, suggesting that the observed response to traffic might have been an artefact of recruitment of age-0 cohorts to the trawl during late summer and early autumn. Seemingly in contrast, Gutreuter et al (2006) found strong evidence that persistent disturbance by shipping caused reductions in the abundances of several species within the navigation channel relative to large secondary channels. That apparent difference is reconciled by differences in measurement.…”
Section: Discussionmentioning
confidence: 93%
“…Current velocity and substrate type within the channel influence the distribution of benthic invertebrates (Fremling 1960, Seagle et al 1982, Anderson and Day 1986, Dettmers et al 2001b, and connectivity with adjacent lentic areas provides important sources of invertebrate drift (Eckblad et al 1984, Sheaffer andNickum 1986b). Hydraulic traps within the river bedform, i.e., sand dunes, support the retention of macroinvertebrate drift (Gutreuter et al 2006) and provide low-velocity refuge and energetic savings for fishes feeding on drift in the main channel (Lehtinen et al 1997, Guensch et al 2001, Wildhaber et al 2003, Gaeuman and Jacobson 2007. Similarly, drift-feeding fishes have been observed to use areas Ecology and Society 23(2): 6 https://www.ecologyandsociety.org/vol23/iss2/art6/ Fig.…”
Section: Fish Communitymentioning
confidence: 99%